2005
DOI: 10.1007/s12111-005-1002-z
|View full text |Cite
|
Sign up to set email alerts
|

The social adjustment of African American females at a predominantly white midwestern university

Abstract: This study examines the social adjustment of African American female students at a predominantly white university in the Midwest. Johnson's (2001) Afrocentric development theory encourages student administrators to examine what African American females say about themselves psychologically and socially. Respondents were chosen via non-probability sampling and answered open-ended questions centering on social adjustment factors. Using content-analysis, the interviews revealed three themes: 1) racial prejudice; 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Research in this area has been scant, although some scholars have called for a new way of looking at retention in African American students. For example, von Robertson et al (2005) suggested the use of the Nguzo Saba as framework for looking at retaining African American students. The Nguzo Saba is based on the idea of using African American-based values to develop African American college students socially and academically, and it incorporates seven principles: umoja (unity), kujichaguila (self-determination), ujima (collective work and responsibility), ujamaa (cooperative economics), nia (purpose), kuumba (creativity) and imani (faith).…”
Section: Implications and Directions For Future Researchmentioning
confidence: 99%
“…Research in this area has been scant, although some scholars have called for a new way of looking at retention in African American students. For example, von Robertson et al (2005) suggested the use of the Nguzo Saba as framework for looking at retaining African American students. The Nguzo Saba is based on the idea of using African American-based values to develop African American college students socially and academically, and it incorporates seven principles: umoja (unity), kujichaguila (self-determination), ujima (collective work and responsibility), ujamaa (cooperative economics), nia (purpose), kuumba (creativity) and imani (faith).…”
Section: Implications and Directions For Future Researchmentioning
confidence: 99%
“…The overall climate at PWIs has not developed to the point where it meets the needs of its ever-growing diverse student population (Adams, 2005;Guiffrida & Douthit, 2010;Strayhorn, 2008);Von Robertson, Mitra, & Delinder, 2005). Race-related stressors have a huge bearing on adult African American womens' academic success (AsburnNardo & Smith, 2008;Neville, Heppner, Ji, & Thye, 2004;Utsey, Ponterotto, Reynolds, & Cancelli, 2000;Williams, Neighbors, & Jackson, 2003) and serves as a constant reminder of her "Blackness" (Guiffrida, 2006;Parker & Flowers, 2003).…”
Section: Racial Bias Within the Pwi Environmentmentioning
confidence: 99%
“…Their success, like all college students, is the foundational philosophical premise for which institutions of higher education exist (Von Robertson et al, 2005). Their success factors are multifaceted and are the result of individual and institutional components that impact their experiences.…”
Section: Significancementioning
confidence: 99%
“…Many of the unique challenges of African American women that have been discussed in the research are related to both race and gender identity (Bowen, 2009;Sims, 2008;Von Robertson et al, 2005;Winkle-Wagner, 2008). Often described as "double jeopardy," "double bind," or "dual burden," Black women may experience more stress than minority men and White women on campus, and differences within groups are often overlooked with studies that focus on either all women, men, or African American students (Winkle-Wagner, 2008).…”
Section: African American Womenmentioning
confidence: 99%
See 1 more Smart Citation